Simulation of CSST’s astrometric capability - Fu, Zhen-Sen; Qi, Zhao-Xiang; Liao, Shi-Long; Peng, Xi-Yan; Yu, Yong; Wu, Qi-Qi; Shao, Li; Xu, You-Hua (Frontiers in Astronomy and Space Sciences, 2023)
The China Space Station Telescope (CSST) will enter a low Earth orbit around 2024 and operate for 10 years, with seven of those years devoted to surveying the area of the median-to-high Galactic latitude and median-to-high Ecliptic latitude of the sky. To maximize the scientific output of CSST, it is important to optimize the survey schedule. We aim to evaluate the astrometric capability of CSST for a given survey schedule and to provide independent suggestions for the optimization of the survey strategy. For this purpose, we first construct the astrometric model and then conduct simulated observations based on the given survey schedule. The astrometric solution is obtained by analyzing the simulated observation data. And then we evaluate the astrometric capability of CSST by analyzing the properties of the astrometric solution. We find that the accuracy of parallax and proper motion of CSST is better than 1 mas($·$ yr$^{-1}$) for the sources of 18-22 mag in g band, and about 1$\sim$10 mas($·$ yr$^{-1}$) for the sources of 22-26 mag in g band, respectively. The results from real survey could be worse since the assumptions are optimistic and simple. We find that optimizing the survey schedule can improve the astrometric accuracy of CSST. In the future, we will improve the astrometric capability of CSST by continuously iterating and optimizing the survey schedule.